Proporsi Dewan Direksi Wanita dan Pengaruhnya terhadap Profitabilitas Perusahaan Sektor Jasa - Yesica Christina Manurung; Feliciana Tjitrohartoko; Yulius Jogi Christiawan (Business Accounting Review, 2020)
This study was conducted to know the effect of the proportion of women in management board on the profitability of service sector firms. This study also used firm size and leverage as control variables. The sample used in this study were 248 service sector listed firms on the Indonesia Stock Exchange (IDX) in 2015-2019. In this study, the proportion of women in management board was measured by dividing the number of women in the management board by the number of all members of the management board. Meanwhile, profitability was measured using Return on Assets (ROA). The data analysis technique used in this research was panel data regression analysis using Gnu Regression, Econometrics and Time-series Library (GRETL) software. The result of this study showed that the proportion of women in management board had a negative and significant effect on profitability. Meanwhile, for the control variable, firm size had a significant positive effect on profitability and leverage had a significant negative effect on profitability.